Model Pengembangan Kurikulum Pendidikan Agama Islam - Utomo, Tri Prasetiyo; Muchklisin, Nur (JOIES (Journal of Islamic Education Studies), 2025)
This research seeks to find a design for the development of the Islamic Religious Education (PAI) curriculum. Education will continue to develop in line with the dynamics of social development in society. With regard to these dynamics, the curriculum which includes, design, implementation, and evaluation (approaches, techniques, and strategies and assessments) will undoubtedly develop or undergo changes. This research uses a qualitative approach to literature types. The research subjects are in the form of curriculum development research results, teacher creativity in developing learning methods, strategies, and approaches. Data collection techniques by looking for books, research journals, and papers that are relevant to curriculum development. Data analysis techniques using interactive analysis. This model begins with data reduction, data display, and conclusion drawing. Research results; First, curriculum design is a drawing of institutional action steps in the form of formulating educational goals, curriculum content, student learning experiences, and learning evaluation techniques. Second, educators' creativity is the learning approach, learning strategies, and methods presented to students, as well as techniques used to create an active, effective, and fun learning atmosphere. Third, the curriculum evaluation model of the assessment process to determine learning success using the measurement model, congruence evaluation model, and illumination evaluation model.